SARS-CoV-2 and endothelial cell interaction in COVID-19: molecular perspectives. (9th February 2021) - Giordo, Roberta; Paliogiannis, Panagiotis; Mangoni, Arduino Aleksander; Pintus, Gianfranco
Abstract : SARS-CoV-2 is the agent responsible for the coronavirus disease (COVID-19), which has been declared a pandemic by the World Health Organization. The clinical evolution of COVID-19 ranges from asymptomatic infection to death. Older people and patients with underlying medical conditions, particularly diabetes, cardiovascular and chronic respiratory diseases are more susceptible to develop severe forms of COVID-19. Significant endothelial damage has been reported in COVID-19 and growing evidence supports the key pathophysiological role of this alteration in the onset and the progression of the disease. In particular, the impaired vascular homeostasis secondary to the structural and functional damage of the endothelium and its main component, the endothelial cells, contributes to the systemic proinflammatory state and the multiorgan involvement observed in COVID-19 patients. This review summarizes the current evidence supporting the proposition that the endothelium is a key target of SARS-CoV-2, with a focus on the molecular mechanisms involved in the interaction between SARS-CoV-2 and endothelial cells.